Implication of population aging on economic growth and saving - wong, Yii Sung (2014)
Based on United Nation projections, world population structure have tendency to move toward the population aging structure. Population aging means increase in median age of population. Reason behind this demographic transition is because of the combination effect from low fertility and longer longevity. Population aging is said would induce several problems to a country in term of theirs macroeconomic, labour market and social security. However, researcher believed impact of aging society may vary depend on economic policies implemented. Effective policies implemented can help in offsetting the effect of population aging. Most of the early studied have utilized panel data in their analysis. Nevertheless, the results can only provide a general conclusion. Some of the population aging effect on individual country may not be well explained. In addition, previous empirical result uncovers the possibility of the existence of nonlinear relationship. Hence, both linear and nonlinear causality test are employed in this thesis to examine the causal relationship among old-age dependency ratio and work to retirement ratio on economic growth as well as on saving. The countries involved in this analysis include Japan, Germany, China, Malaysia and Singapore. Findings suggested that economic policies implemented do affect the impact of the population aging. Japan seems to have better policies in dealing with the aging society. Result also show that adjustment on retirement age gives significant effect on economic growth and saving. Besides, few cases show the existence of nonlinear causal relationship. Therefore, nonlinear relationship should also be considered to avoid bias result.